Integrating family planning with genitourinary medicine: Developing an holistic sexual health clinic in Eastbourne. Issue 4 (1st October 2000) - Jones, Martin
Abstract : The idea of providing family planning and genitourinary medicine under one roof has attracted much interest. The development of an integrated sexual health clinic in Eastbourne is described, from initial discussions between disparate parties to the emergence of a one-stop-shop, with a look to the future.